Catabolism of sialic acids in an environmental microbial community. Issue 5 (21st April 2022) - Tomás-Martínez, Sergio; Chen, Le Min; Neu, Thomas R; Weissbrodt, David G; van Loosdrecht, Mark C M; Lin, Yuemei
Abstract: Sialic acids are a family of nine-carbon negatively charged carbohydrates. In animals, they are abundant on mucosa surfaces as terminal carbohydrates of mucin glycoproteins. Some commensal and pathogenic bacteria are able to release, take up and catabolize sialic acids. Recently, sialic acids have been discovered to be widespread among most microorganisms. Although the catabolism of sialic acids has been intensively investigated in the field of host–microbe interactions, very limited information is available on microbial degradation of sialic acids produced by environmental microorganisms. In this study, the catabolic pathways of sialic acids within a microbial community dominated by ' Candidatus Accumulibacter' were evaluated. Protein alignment tools were used to detect the presence of the different proteins involved in the utilization of sialic acids in the flanking populations detected by 16S rRNA gene amplicon sequencing. The results showed the ability of Clostridium to release sialic acids from the glycan chains by the action of a sialidase. Clostridium and Chryseobacterium can take up free sialic acids and utilize them as nutrient. Interestingly, these results display similarities with the catabolism of sialic acids by the gut microbiota. This study points at the importance of sialic acids in environmental communities in the absence of eukaryotic hosts. Abstract : Catabolism of sialic acids in a microbial community with no host–microbe interaction resembles the one described for gut microbiota.